Benefits and risks of fish consumption for the human health - Ana Carolina Fernandes (Revista de Nutrição, 2012)
The article aimed at identifying and discussing scientific evidences on the benefits and risks of fish consumption the human health. There was a systematic survey for articles published from 2003 and May 2011, at the MedLine, Scopus, SciELO, Lilacs and Google Scholar databases. The key words used were: fish, food intake, omega-3 fatty acids, fatty fish, benefits, risk, and consumption. The search produced 12,632 articles, 25 eligible cohort studies on possible benefits, 61 on risks and 10 studies that assessed the "risk/benefit" relation. Of the 25 works, 14 suggested a preventive effect of fish consumption related to cardiovascular diseases, depression, cataract and some types of cancer. Evidences of a relation between exposure to mercury and an increase in the risk of neurological disorders, but not of cardiovascular diseases, were also found. Given the importance of fish consumption, its possible risks and the lack of Brazilian studies on the topic, it is important to conduct more longitudinal studies that assess both the benefits and risks of fish consumption for the human health. We also emphasize the need for policies to reduce exposure of fish and seafood to mercury and other contaminants.